The Potential of Millennial Muslim’s Halal Tourism During The Covid-19 Pandemic - Susilawati, Cucu; Abduh, Muhamad; Kamaruddin, Muhammad Iqmal Hisham; Sari, Rosi Hasna (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2022)
This research is motivated by the trend of increasing the tourism sector to 16.11 million people in 2019, which makes halal tourism such as one of the profitable industries in the global market. However, since the confirmed case of Covid-19 in March 2020, the tourism sector has decreased by 66.02% in April 2020. It is known that tourists visiting during the COVID-19 pandemic are tourists from the millennial generation. This study aims to find out how to implement halal tourism in Indonesia and to find out how the millennial generation has the potential to increase halal tourism during the Covid-19 pandemic. This study uses a mixed-method i.e. a combination of quantitative and qualitative. Based on the distribution of questionnaires to 300 respondents, the results stated that the millennial generation was interested in and carried out halal tourism. The conclusion is the millennial Muslim generation continued to carry out tourism during the pandemic by implementing strict health protocols. This research implies that halal tourism can still revive even though a pandemic hits it.